Progress in the treatment of lung adenocarcinoma by integrated traditional Chinese and Western medicine - Jiang, Hongxin; Bu, Lina (Frontiers in Medicine, 2024)
Non-small cell lung cancer (NSCLC) overwhelmingly represents the predominant histological subtype of lung cancer, with lung adenocarcinoma emerging as the most prevalent form. Conventional Western medical treatments encompass a spectrum of modalities, including surgical interventions, cytotoxic chemotherapy, radiotherapy, targeted pharmacotherapy, and immunotherapy. In contrast, Traditional Chinese Medicine (TCM) methodologies encompass traditional Chinese medicine treatments, acupuncture therapies, and tuina treatments. While conventional Western medicine has made remarkable strides in the treatment of lung cancer, it is important to acknowledge the limitations inherent in singular treatment approaches. Consequently, the quest for a more comprehensive and integrative therapeutic paradigm becomes imperative. A deficiency of evaluation criteria specific to lung adenocarcinoma treatment in the realm of TCM represents an outstanding challenge in need of resolution. Nonetheless, in the backdrop of the continuous evolution of lung adenocarcinoma treatment modalities, the amalgamation of Chinese and Western medical approaches for treating this condition has exhibited a promising trajectory. It not only contributes to mitigating toxicity and augmenting efficacy but also serves to reduce a spectrum of postoperative complications, thereby enhancing the quality of patients’ survival and extending life expectancy. This article furnishes a comprehensive survey of the research advancements in the integration of Chinese and Western medical approaches for treating lung adenocarcinoma. It elucidates the merits and demerits of individual and combined therapeutic strategies, surmounts current limitations, underscores the virtues of amalgamating Chinese and Western medical paradigms, and offers a more holistic, integrated, and efficacious treatment blueprint.